"Communication is taking a back seat": speech pathologists' perceptions of aphasia management in acute hospital settings. Issue 5 (3rd May 2016) - Foster, Abby; O'Halloran, Robyn; Rose, Miranda; Worrall, Linda
Abstract : Background : Current service provision to people with aphasia in the acute hospital setting is reported to be inconsistent with best-practice recommendations. While speech pathologists (SPs) have been noted to express dissatisfaction with this, the underlying reasons for this evidence–practice gap are unclear. Change is required in order to move towards the provision of gold-standard aphasia management in acute hospitals. The voices of SPs working in this setting, and knowledge of their perceptions of the factors that influence their current practice, are essential in order to facilitate their capacity to act as agents for change. Aims : This research explored acute SPs' conceptualisation, experiences, and perceptions of poststroke aphasia management, and provided a greater understanding of the factors that influence their practice. Methods & Procedures : A purposive, maximal variation technique was used to sample SPs. Semistructured in-depth interviews were conducted with 14 SP participants who work with people with acute poststroke aphasia. Inductive thematic analysis was used to analyse the results. Outcomes & Results : Analysis yielded five key themes. As a result of undertaking this research, insight was gained into (1) acute SPs' perception of their role in relation to acute aphasia management; (2) the professional tension created by competing priorities; (3) the de-prioritisation of aphasia in relation to dysphagia management; (4) SPs' beliefs about aphasia and their current aphasia management; and (5) their understanding of facilitators for acute aphasia management. Conclusions : This study elucidated the complex and multifaceted nature of the factors influencing SPs' management of aphasia in the acute health care setting. Findings included the identification of modifiable factors—such as supportive practice environments, locus of control, and reflective practice—which facilitate evidence-based approaches to aphasia management in that acute hospital setting.